Pengaruh Kecerdasan Emosional dan Kemandirian Belajar terhadap Kemampuan Literasi Matematis - Difa Salsabila Fauziah C.A; Sarwo Edy; Sri Suryanti (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to determine the effect of emotional intelligence and self-regulated learning on mathematical literacy ability. This research is a quantitative survey method with path analysis technique. The population in this research was about 574 students and the sample used was 236 students in grade VIII at the State Junior High School in Kebomas District. The research instruments used were emotional intelligence questionnaire, self-regulated learning questionnaire, and mathematical literacy test. The data analysis method used for this research is path analysis using SEM (Structural Equation Modeling) with a significance level of about 5% using the AMOS 26 application. The results revealed that (1) there is a significant positive influence between emotional intelligence on mathematical literacy ability, (2) there is a significant positive influence between self-regulated learning on mathematical literacy ability, (3) there is a significant positive influence between emotional intelligence and self-regulated learning. The results of this research contribute to the development of the science of learning psychology towards 21st century skills.